Effect of Supplementation ARA (Arachidonic acid) Oil on Production Performance, Egg quality and Fatty Acid Composition in Laying Hens - Purba, Dian Rizki; Xiao-guang Dong; Jing Wang; Hai-jun Zhang; Guang-hai Qi; Shu-geng Wu (International Journal of Science, Technology & Management, 2021)
The effect of supplementation ARA oil on production performance, egg quality, fatty acid composition in laying hens were examined on this study. The aims on this study to producing ARA enriched eggs to meet infant nutrition requirements. A total of 450 Roman White laying hens with a similar egg production rate and good body condition at 55 weeks of age were randomly divided into 5 treatments. Each treatment was replicated 6 times with 15 hens per replicate. Hens were fed basal diets with 0, 2,5%, 1,25%, 0,625%, and 0,3125% ARA oil addition. The supplementation ARA oil was effect to decreased egg production, egg weight, egg mass, daily feed intake and FCR (P<0.05) during 9-12 week, but on egg quality parameters showed slightly changed during the 1-12 week but not consistency and that change was not statistically significant. Arachidonate acid (ARA) was increased by supplementation ARA oil (P<0.05). This effect was detected in directly proportional to the addition of ARA oil on diet. This is opposite effect to DHA, DHA was decreased by supplementation ARA oil (P<0.05) and also effect to ratio ARA/DHA was increased (P<0.05) by supplementation ARA oil.